2022
DOI: 10.3390/bs12010013
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Pandemic in a Vulnerable Population: Prevalence and Correlates of Anxiety

Abstract: Background: The COVID-19 pandemic has produced negative mental health outcomes. These effects were more prominent in vulnerable communities that experienced prior similar disasters. The study aimed to examine the likelihood and correlates of anxiety symptoms among Fort McMurray (FMM) residents, during the COVID-19 pandemic. Methods: A cross-sectional online survey questionnaire was applied between 24 April and 2 June 2021, at FMM, to gather sociodemographic, COVID-19, and clinical information, including genera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 33 publications
1
5
1
Order By: Relevance
“…Previous studies agree with our finding, which suggested that increased social support protects against mental health effects, increases resilience, and improves coping post-natural disasters [ 30 , 31 , 32 ]. Low levels of social support are also associated with post-disaster psychological symptoms and mental health disorders [ 13 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Previous studies agree with our finding, which suggested that increased social support protects against mental health effects, increases resilience, and improves coping post-natural disasters [ 30 , 31 , 32 ]. Low levels of social support are also associated with post-disaster psychological symptoms and mental health disorders [ 13 ].…”
Section: Discussionsupporting
confidence: 93%
“…Low levels of social support are also associated with post-disaster psychological symptoms and mental health disorders [ 13 ]. Furthermore, receiving absolute social support is protective against psychological distress following flooding and other natural disasters [ 31 ]. However, community, social, and governmental support play a vital role in resiliency.…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, FMM was heavily affected by the COVID-19 pandemic [26]. The COVID-19 pandemic may profoundly affect an individual's physical and mental health [27,28]. Physical distancing and sanitation measures of COVID-19 also posted further challenges on evacuation, post-disaster regulation and recovery [29].…”
Section: Disaster Events and People In Fort Mcmurraymentioning
confidence: 99%
“…For analysis purposes, the scores were recategorized into two groups: none to mild anxiety (<10) and moderate to severe anxiety (≥10). The GAD-7 is a valid scale used to screen and assess the severity of anxiety symptoms in both clinical field and research [ 25 , 26 ]. The tool has good test–retest reliability (intraclass correlation = 0.83) with excellent internal consistency (Cronbach α = 0.92) [ 5 , 25 , 27 ].…”
Section: Methodsmentioning
confidence: 99%